1995
DOI: 10.1021/bi00036a039
|View full text |Cite
|
Sign up to set email alerts
|

Calcium involvement in aminophospholipid exposure and microparticle formation during platelet activation: A study using Ca2+-ATPase inhibitors

Abstract: The development of procoagulant activity and microparticle formation during platelet activation is known to depend on an increase in cytosolic Ca2+ levels. We have studied the mechanisms leading to these events using FITC-labeled recombinant annexin V, a protein which binds with a high affinity to aminophospholipids, in flow cytometry. In particular, we show that the Ca(2+)-ATPase inhibitors thapsigargin and cyclopiazonic acid are as potent inducers of aminophospholipid exposure and microparticle formation as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
155
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(175 citation statements)
references
References 49 publications
19
155
1
Order By: Relevance
“…One study showed a marked diminishment in Foxp3 mRNA up-regulation after TGF-␤ induction of peripheral T cells stimulated in the presence of anti-CD28 Abs (7). In contrast, a second study found that CD28 costimulation was important for Foxp3 expression in TGF-␤-treated CD4 ϩ CD25 Ϫ thymocytes, primarily by enhancing cell survival (42). In multiple experiments using highly purified Ab-stimulated T lymphocytes, we failed to observe either a beneficial or deleterious role for CD28 costimulation in Foxp3 up-regulation.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…One study showed a marked diminishment in Foxp3 mRNA up-regulation after TGF-␤ induction of peripheral T cells stimulated in the presence of anti-CD28 Abs (7). In contrast, a second study found that CD28 costimulation was important for Foxp3 expression in TGF-␤-treated CD4 ϩ CD25 Ϫ thymocytes, primarily by enhancing cell survival (42). In multiple experiments using highly purified Ab-stimulated T lymphocytes, we failed to observe either a beneficial or deleterious role for CD28 costimulation in Foxp3 up-regulation.…”
Section: Discussioncontrasting
confidence: 65%
“…Circulating microparticles may be derived from leukocytes (40), endothelial cells (41), platelets (42), or RBC (43). The particles carry bioactive molecules that deliver intercellular signals (42). They are thought to have important proinflammatory and procoagulatory roles (44,45), including promoting interaction between endothelial cells and monocytes (40), platelet activation (46), and apoptosis (47).…”
Section: Discussionmentioning
confidence: 99%
“…In experiments performed to control the extent of platelet activation, whole blood was also collected in the presence of inhibitors of platelet activation (theophylline, adenosine, and dipyridamole [CTAD] tubes, Becton Dickinson). To assess platelet activation, flow cytometry was performed on whole blood with the following monoclonal antibodies: VH10, 8 recognizing P selectin; PAC-1 (Immunotech, Marseille, France); and AP6 (gift from Dr T.S. Kunicki), 9 recognizing the active conformation of glycoprotein IIbIIIa.…”
Section: Blood Sampling and Plasma Preparationmentioning
confidence: 99%
“…PS can also be exposed by red ~lood cells and is involved in their clearance from circulation 11]. Platelet activation causes rapid increase in intracellular 2a 2+, and pharmacological modulation with Ca 2+ ionophores ~r Ca2+-ATPase inhibitors can stimulate the exposure of large lmounts of PS by platelets within minutes [12]. Ca 2+ inacti- vates the aminophospholipid translocase which normally constrains PS to the inner leaflet [13], but this alone is insufficient for exposure.…”
Section: ~ Introductionmentioning
confidence: 99%